A survey on anti-diabetic medication adherence among Type 2 diabetics in a public hospital in Selangor - Lee, Khuan; Abdullah, Nor Fadhilah; Sowtali, Siti Noorkhairina; Juni, Muhamad Hanafiah; Anthony Abdullah, Muhammad Mikhail Joseph; Abdullah, Steven Eric Krauss @ Abdul Lateef; Mat Yusoff, Rozainah (2017)
Objective: This study was conducted to determine the adherence rate and adherence pattern to anti-diabetic medications among patients undergoing Type 2 diabetes treatment in a public hospital in Selangor, Malaysia. Methods: A cross sectional descriptive survey was done based on 200 randomly selected patients from a public health hospital in Malaysia. Data was collected using questionnaire guided face to face interview. Adherence was measured by using the Medication Compliance Questionnaire (MCQ) which consists of a total of seven questions. Data was analysed using univariate analysis to summarize data; and bivariate analysis with 95% Confidence Interval (CI) to determine the pattern of adherence with a p-value < 0.25. Results: A low medication adherence rate of only 57.0% was found. Race, duration of illness and having taken Dipeptidil Peptidase-4 (DPP-4) inhibitor medication medication were significantly associated with medication adherence. Conclusion: The medication adherence rate was low among diabetes patients. This is alarming, because non-adherence could lead to poor glycaemic control that cause complications that cause complications of diabetes and increase mortality rate. Nurses play an important role to initiate medication adherence education that tailored to patient needs to adhere to anti-diabetic medication.